The acoustic playback technique in avian fieldwork contexts: a systematic review and recommendations for best practice - De Rosa, Alberto; Castro, Isabel; Marsland, Stephen (Ibis (London, England), 2022)
Acoustic playback is commonly used to study wild birds, with applications as diverse as investigating behaviours, ascertaining the presence of rare and elusive species, and attracting individuals to a location. The number of studies employing playback is growing larger every year because it is easy to apply, increasingly affordable and very effective. However, the way that it is used and reported varies significantly across researchers and species. This lack of a protocol for reporting acoustic playbacks inevitably slows the progress of the field, as studies cannot be easily compared. In 1991, some of the most knowledgeable researchers in the field of animal communication met at a North Atlantic Treaty Organization (NATO) Advanced Research Workshop (ARW) at Thornbridge Hall in the UK to consider the design of playback experiments. The proceedings of the meeting were published in 1992 and contain crucial guidelines regarding this use of playback. In this paper we review the literature for papers published since that milestone that use acoustic playback in ornithological fieldwork contexts. We use the RepOrting standards for Systematic Evidence Syntheses (ROSES) to evaluate the description of the methods used. The main goal of this review paper is to identify a shared set of rules for employing and reporting the playback technique in such contexts to promote reproducibility and comparability. We found 625 peer‐reviewed articles in three on‐line databases, of which 419 reported field (rather than captive) studies employing avian playback. The biggest hindrance to reproducibility is the availability of the acoustic tracks used by authors; 4% (15 articles) of our sample made their tracks publicly available. We found that only one article provided enough details for their playback application to be fully reproducible. Further, only five articles (0.92%) provided enough information for reproducibility, even if we assume information about track preparation and recording details to be unnecessary when tracks are available. Based on our synthesis of the literature, we provide a set of recommendations for the reporting of playback uses to promote reproducibility, including sample paragraphs of description as supplementary material. We strongly recommend that tracks used for such experiments are deposited in dedicated on‐line repositories for the use of other researchers. While our focus is avian fieldwork applications of the playback technique, we believe that our findings can be easily transferred to other animal systems subject to acoustic playback.